PENGARUH IKLIM BELAJAR DAN INTERAKSI GURU TERHADAP PARTISIPASI MURID PADA PEMBELAJARAN SKI - RANI NUR ROCHMA; MAHMUD; Fairuz Zubady Al Farizy (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2026)
ABSTRACT This study aims to examine the effect of the learning climate on students' participation, the effect of teacher interaction on students' participation, and the simultaneous effect of the learning climate and teacher interaction on students' participation in Islamic Cultural History (SKI) learning. The study employed a quantitative approach using an ex post facto research design. Out of a population of 409 eleventh-grade students at MAN 1 Mojokerto, 123 respondents were drawn as the sample using proportional random sampling. A questionnaire was used to gather the data, which were then processed through multiple linear regression assisted by IBM SPSS Statistics 27. The findings indicate that both the learning climate and teacher interaction have a positive and statistically significant effect on students' participation. The learning climate significantly influences students' participation (t = 9.427 > 1.980; p = 0.000), and teacher interaction also has a significant effect on students' participation (t = 9.014 > 1.980; p = 0.000). Simultaneously, the two independent variables have a significant effect on students' participation (F = 52.755 > 3.07; p = 0.000). The resulting regression equation is Ŷ = 8.555 + 0.426X₁ + 0.314X₂, with a correlation coefficient (R) of 0.684 and a coefficient of determination (R²) of 0.468. These results indicate that 46.8% of the variance in students' participation is explained by the learning climate and teacher interaction, whereas the remaining 53.2% stems from other variables outside this study's scope.